An assessment of structure and contents quality of informed consent forms in Lambayeque Region, March-June 2010 - Castro Maldonado, Betty (2010)
Objective: To determine the quality of informed medical consent forms (ICFs) used in different hospitals in Lambayeque region with respect to their structure and contents Material and method: This was a descriptive, cross-sectional and observational study. ICFs used in Lambayeque hospitals were assessed with respect to their quality of structure and contents with the participation of Ethics Committees. Two categories were established: complied (if the forms were complete and detailed); or non-compliant (because of omission or confounding). Forms were divided according to the number of requisites complied with: more than 75% (complying with 19-24 requisites); between 50 to 75% (12 to 18 requisites) and less than 50% (0 to 11 requisites).   Results: Of the eight forms studied in the Hospitals of the Region Lambayeque found in no (0%) were eligible hospital of failing to model more than 75% (19-24 requirements), 1 (12.5%) hospitals was found between 50 and 75% (12-18 requirements) and in six hospitals (75%) had less than 50% (0-11 requirements). Conclusions: The quality of ICFs in Lambayeque region in terms of their structure and contents is poor.